Vertical Profile of Phytoplankton Abundance in Tanjung Putus Oxbow Lake Buluh Cina Village Siak Hulu Sub District Kampar District Riau Province - Simanjuntak, Debora Melani; Simarmata, A. H.; Sihotang, Clemen (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in February 2013 at Tanjung Putus Oxbow Lake.Phytoplankton samples were collected from 3 stations. In each station, there were 2sampling sites, in the surface and in 2.5 Secchi depth. Sampling was done three times,once a week. Objective of this research was to find-out the vertical profiles ofphytoplankton abundance in Tanjung Putus Oxbow Lake. Results of this researchrevealed 47 species of phytoplankton were classified into 5 classes, namely, Chlorophyceae(14 species), Cyanophyceae (6 species), Bacillariophyceae (10 species), Chrysophyceae (1species), and Xanthophyceae (5 species). The phytoplankton abundance at surface rangedfrom 221634-361213 cells/l and in 2.5 Secchi depth ranged from 135814-216923 cells/l. Thevertical profile of phytoplankton abundance was higher in surface than that in 2.5 Secchidepth. The water quality parameters such as water temperature ranged from 30-31oC,transparancy from 89-92.3 cm, depth from 141.7-301.7 m, pH 5.0, dissolved oxygen from3.50-6,17 mg / l, free carbon dioxide from 7.76-15.7 mg / l, nitrate from 0.02-0.1 mg / l, andphosphate ranged from 0.020-0.1 mg / l. Based on phytoplankton abundance, Tanjung PutusOxbow Lake was categorized mesotrophy.Key words : Phytoplankton, the vertical profiles, Tanjung Putus Oxbow Lake